Withholding and withdrawal of life-sustaining therapy in terminally ill children with cancer: A position statement by the PHO chapter of the Indian Academy of Pediatrics - Vikramjit S. Kanwar; Poonam Bagai; Anupama Borker; Veronique Dinand; Roop Gursahani; Krutika Kurhade; Manas Kalra; Smriti Khanna; Manjusha Nair; Amita Mahajan; Gayatri Palat; Raghwesh Ranjan; et al. (Elsevier, 2024)
In the last four decades, survival in childhood cancer in India has improved significantly, however we increasingly face the question that has challenged providers in high-income countries: when care becomes futile and merely prolongs suffering, how should that be addressed? This position statement was prepared by a panel in the Pediatric Hematology-Oncology chapter of the Indian Academy of Pediatrics (IAP-PHO), with external experts, using a process endorsed by the Executive Committee of IAP-PHO. The panel consisted of providers and stakeholders who were committed to improving end-of-life care (EOLC) in children with cancer. Three case scenarios of terminally ill children with cancer were presented, and the various challenges of EOLC in each situation were brought up, including families who wanted everything possible done for their child and the fear of medicolegal issues by physicians. We emphasize the importance of involving palliative care services early in the process to ensure that families receive a consistent message about their child's outcome. With the recent Supreme Court of India decision, there is now a viable EOLC pathway to withdraw life-sustaining therapy (LST) from children who are terminally ill. We outline it and discuss the various barriers to the withdrawal of LST. Increased access to palliative medicine services, which currently exist sporadically across India, is a core necessity. IAP-PHO hopes to actively work with organizations representing colleagues in palliative care and intensive care, to see how we can improve EOLC in childhood cancer.